2008
DOI: 10.1080/15226510801913918
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution in Aquatic Ecosystems and its Phytoremediation using Wetland Plants: An ecosustainable approach

Abstract: This review addresses the global problem of heavymetal pollution originating from increased industrialization and urbanization and its amelioration by using wetland plants both in a microcosm as well as natural/field condition. Heavymetal contamination in aquatic ecosystems due to discharge of industrial effluents may pose a serious threat to human health. Alkaline precipitation, ion exchange columns, electrochemical removal, filtration, and membrane technologies are the currently available technologies for he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
139
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(157 citation statements)
references
References 158 publications
0
139
0
6
Order By: Relevance
“…If the capacity of CWs to depurate waters from bulk pollutants and nutrients is generally recognized, recent research has been directed to the removal of other contaminants such as metals and organic micropollutants from several types of wastewaters (Matamoros et al, 2008;Rai, 2008;Imfeld et al, 2009;Park et al, 2009;Avila et al, 2010;Marchand et al, 2010;Breitholtz et al, 2012). In particular, several studies showed successful applications of CWs to remove hardly biodegradable organic xenobiotic compounds such as pesticides and pharmaceuticals (Cheng et al, 2002;Matamoros et al, 2008Matamoros et al, , 2012aDordio et al, 2009bDordio et al, , 2010Avila et al, 2010;Hijosa-Valsero et al, 2011;Agudelo et al, 2012;Warsaw et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If the capacity of CWs to depurate waters from bulk pollutants and nutrients is generally recognized, recent research has been directed to the removal of other contaminants such as metals and organic micropollutants from several types of wastewaters (Matamoros et al, 2008;Rai, 2008;Imfeld et al, 2009;Park et al, 2009;Avila et al, 2010;Marchand et al, 2010;Breitholtz et al, 2012). In particular, several studies showed successful applications of CWs to remove hardly biodegradable organic xenobiotic compounds such as pesticides and pharmaceuticals (Cheng et al, 2002;Matamoros et al, 2008Matamoros et al, , 2012aDordio et al, 2009bDordio et al, , 2010Avila et al, 2010;Hijosa-Valsero et al, 2011;Agudelo et al, 2012;Warsaw et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical approaches have been widely used for remedying polluted soil and water. However, they experienced more difficulties for a large scale of remediation because of high initial capital cost, larger volume of chemicals, continuous maintenance, skilled technicians and even generate large amount of sludge which adds into the secondary waste generation, posing threats to aquatic life and minimizes the acceptability of the treatment technique (Rai, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several other large natural inputs of heavy metals into water ecosystems are from the erosion or rocks, wind-blowing dusts, volcanic activity, and forest fires [128]. In addition, several anthropogenic activities such as energy production technologies, industrial effluents, and wastes (from coal mines, thermal power plants, metallurgy, plating, chemical plant, curry and paper-making industries, and other allied industries) alter the physicochemical characteristics of water bodies and elevate the heavy metals concentration according to the nature of effluent being discharged [130,131]. Therefore, aquatic ecosystems receive inputs of different source containing a variety of metal ions (M x+ )…”
Section: Heavy Metals and Metalloidsmentioning
confidence: 99%